The relationship between subclinical hypothyroidism and invasive papillary thyroid cancer - Li, Changlin; Zhang, Jiao; Dionigi, Gianlorenzo; Sun, Hui (Frontiers in Endocrinology, 2023)
Background: Subclinical hypothyroidism is the most common thyroid dysfunction.Approximately 10% of patients with thyroid cancer have subclinical hypothyroidism. There is a paucity of real-world studies examining the relationship between subclinical hypothyroidism and known correlates of invasiveness of papillary thyroid carcinoma (PTC).A retrospective cohort study of 13,717 patients with PTC was conducted. Odds ratios were calculated to assess the relationship between subclinical hypothyroidism and extrathyroidal extension (ETE) after adjusting for BMI and genders. The Cancer Genome Atlas (TCGA) data were utilized for the analysis of TSHR-associated pathways, while qRT-PCR was employed to validate the expression levels of pivotal genes in the relevant signaling pathways.In total, 13,717 PTC patients (10,769 women and 2,948 men; mean [SD] age, 42.90 [9.43] years) were included in the retrospective study. Subclinical hypothyroidism was an independent risk factor for ETE (OR adjusted, 1.168 [95% CI, 1.028-1.327]; P=0.017). In normal-weight patients, subclinical hypothyroidism was an independent risk factor for ETE (OR adjusted, 1.287 [95% CI, 1.089-1.520]; P=0.003). However, this risk was not observed in under-weight, overweight, and obese patients. Compared to females, subclinical hypothyroidism was a higher risk factor for ETE in male patients with normal body weight (OR male=2.363 vs. OR female=1.228). Subclinical hypothyroidism was found to be a significant risk factor for ETE in the subgroup of patients younger than 38 years old (OR1 adjusted, 1.382 [95% CI, 1.032-1.852], P=0.030). The findings from Gene Set Enrichment Analysis (GSEA) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed the involvement of the autophagy signaling pathway in TSHR/ETE/EMT regulation. Moreover, the gene expression levels demonstrated a concentration-dependent relationship between TSH intervention levels and the expression of key genes in the autophagy pathway of thyroid cancer cells.Conclusions: Subclinical hypothyroidism was an independent risk factor for ETE in patients with PTC. This association was particularly significant in normal-weight and younger patients. The risk of ETE associated with subclinical hypothyroidism was higher in males compared to females. Our study indicates a potential involvement of the autophagy pathway in regulating the ETE phenotype in thyroid cancer, specifically in the context of subclinical hypothyroidism.